Downregulation of Jumonji-C domain-containing protein 5 inhibits proliferation by silibinin in the oral cancer PDTX model - Yang, Cheng-Yu; Tsao, Chang-Huei; Hsieh, Cheng-Chih; Lin, Chih-Kung; Lin, Chun-Shu; Li, Yu-Hsuan; Chang, Wei-Chin; Cheng, Jen-Chen; Lin, Gu-Jiun; Sytwu, Huey-Kang; Wang, Yin-Lai; Chen, Yuan-Wu (PLOS ONE, 2020)
Dysregulation of histone demethylase Jumonji-C domain-containing protein 5 (JMJD5) has been identified as a great effect on tumorigenesis. Silibinin is a commonly used anti-hepatotoxic drug and exhibits anticancer effect in various cancers. However, the antitumor mechanism between silibinin and JMJD5 in oral squamous cell carcinoma (OSCC) remains unclear. In this study, the clinical significance of JMJD5 on OSCC patients was assessed through tissue microarray. Furthermore, mice bearing patient-derived tumor xenografts (PDTXs) and tongue cancer cell lines were treated with silibinin and evaluated for tumor growth and JMJD5 expression. High expression of JMJD5 in oral cancer was significantly associated with tumor size (P = 0.0241), cervical node metastasis (P = 0.0001) and clinical stage (P = 0.0002), was associated with worse survival rate compared with that of the total cohort (P = 0.0002). Collectively the data indicate that JMJD5 expression may be suitable for detection of unfavorable prognosis in OSCC patients, based in part on its apparent role as a marker of metastasis. In addition, silibinin inhibits cancer growth in vitro and in PDTX models. Furthermore, metastasis-associated protein 1 (MTA1) could regulate the expression for JMJD5 and had a positive correlation with JMJD5. Moreover, silibinin could downregulate JMJD5 and MTA1 in oral cancer. Present study thus identifies that JMJD5 might be an essential prognostic indicator and therapeutic target against OSCC progression. In addition, silibinin is a potential candidate among novel chemotherapeutic agents or adjuvants for modulating JMJD5 in OSCC, through a mechanism likely involving MTA1/JMJD5 axis.